A arquitetura da ficção científica: o desenho do imaginário para a projeção do real - Cristiana Sofia dos Santos Morgado (2023)
The present dissertation is based on the study of the architecture present in science fiction cinema, intending to show its relevance and the way in which, not only, is presented in architecture as we know it, but also how it affects the way we experience the history on screen. Besides understanding its importance in the cinematographic context, I also seek to highlight its connection with architecture. This relationship can be observed more directly, through the appearance of works of architecture as sets in cinema, or in a more subtle way, through the discreet presence of architectural references in cinema, as well as cinema in architecture. In addition to becoming relevant for the present, this type of architecture proves to be significant for future architecture, corresponding to the space architecture, a new subject that is in constant development, which has caught the attention of architecture firms such as Foster & Partners and BIG. The architect's role becomes crucial in this new discipline, managing to reconcile the needs for human well-being with the demands of an extreme environment. Through a final project, I connect the previous study that was made, by having a direct contact with the influence that the fictitious design has on architecture but, also, conceive a first concept for an architecture of the future, which is space architecture.